"I'm just as Rock 'n' Roll fan". Popular music as a meaning resource for aging - Joseph A. Kotarba (Pontifícia Universidade Católica do Rio Grande do Sul, 2009)
Critics and fans alike have traditionally viewed popular music, especially in terms of its rock'n'roll iterations, as a meaning resource for youth navigating through adolescence. The purpose of this paper is to discuss the relevance of popular music for self-identity through middle age and beyond. The theoretical basis for this exploration is a composite of ideas from existential social thought and symbolic interactionist views on aging. Existential social thought tells us that the process of self-development is constant throughout life. What changes are life circumstances, the biological and affective aging process, reassessment of the past, and strategic relationships with others. The "baby boomer" generation was the first western generation to grow up entirely in the world of rock 'n' roll music and culture, and many baby boomers experienced rock 'n' roll as a master script for life. Therefore, this highly self-integrated cultural resource, enhanced by the power of the mass media, remains central to the self-identity of many baby boomers as they approach old age. The author investigates the variety of ways aging baby boomers keep rock 'n'roll in their lives, with a pervasive interest in the authenticity of their music. Examples include the purchase and display of satellite radio and other status-enhancing technology; the use of rock 'n' roll music to nurture romance and intimacy; appreciation for pop music at religious services and during spiritual experiences; the use of rock 'n' roll to make sense of political issues, and grandparenting-through-Hannah Montana.